Strategi Peningkatan Budaya Pelaporan Patient Safety di Rumah Sakit - Sisilia Somania; Suni Hariati; Syahrul Syahrul (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to summarize previous research findings on strategies to enhance patient safety reporting culture in hospitals using a literature review method through searching seven databases (PubMed, EBSCOhost, ProQuest, ScienceDirect, Garuda, and Google Scholar) spanning from 2013 to 2023. Result, Ten studies met the criteria, resulting in the identification of eleven strategies to enhance patient safety reporting culture in hospitals. These strategies include: feedback, interprofessional collaboration and communication, non-punitive response to errors, clear standards or guidelines, patient safety training, simplification of procedures, increasing nurse awareness and socialization of mandatory reporting incidents, implementing a learning from mistakes approach, transparency, implementation of an implementation framework, and expectations and promotion of patient safety by superiors. In conclusion, this review provides evidence regarding strategies to improve patient safety reporting culture in hospitals, where the most reported strategy is feedback; interprofessional cooperation and communication; non-punitive response to mistakes; and clear guidelines regarding reporting. Keywords: Patient Safety Culture; Hospital; Improvement Strategy